PENGEMBANGAN MEDIA HEBER (HEWAN BERHITUNG) PADA MATERI PERKALIAN KELAS IIII SEKOLAH DASAR - Selly Alvira, Yolanissa; Amir Soleh, Dudung; Imaningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on the analysis of the problem, it shows that difficulties in understanding the concept of multiplication among students are caused by various factors, including the use of inadequate learning media, a teaching approach that focuses on memorization, a lack of conceptual understanding, and low student motivation. The sample in this study consisted of 32 third-grade students at SDN Gondangdia 01 Pagi. This study aims to develop HEBER (animal counting) media for third-grade multiplication material, validate HEBER (animal counting) media for third-grade multiplication material, assess the practicality of HEBER (animal counting) media for third-grade multiplication material, and evaluate the effectiveness of HEBER (animal counting) media for third-grade multiplication material. This study used the Borg & Gall model, which consists of 10 stages, namely potential and problems, data collection, product design, design validation, design revision, preliminary testing, product revision, usage testing, product revision, and mass production (Sugiyono, 2025). This development research used the model. The results showed that the validity of the HEBER (Counting Animals) media from the media expert validation results obtained a score of 100% in the very feasible criteria, while the material expert validation obtained a score of 89.09% with the very feasible criteria. The practicality of the HEBER (Counting Animals) media from the results of teacher practicality obtained a score of 93.33% in the very practical category, the practicality of individual testing (one to one) obtained a score of 100% in the very good category, and small group testing obtained a score of 100% in the very good category. The effectiveness of the HEBER (Counting Animals) media in the field test scored 78% with the category of effective.